Is intra-industry trade specialization a precondition to business cycle synchronization when joining the Euro Area? The Case of Poland - Elżbieta Kawecka-Wyrzykowska (International Journal of Management and Economics, 2017)
The first objective of this paper is to present theoretical approaches to the impact of trade growth (induced by monetary integration) on business cycle synchronization which is an important factor of a country's readiness for a currency union accession. The main conclusion from the first part of the analysis is that business cycle convergence and the cost of the lack of an autonomous monetary policy depend on intra-industry trade (IIT) intensity rather than on general trade growth. The second objective is to assess - using the IIT index as a measure of business cycle synchronization (and of susceptibility to asymmetric shocks transmitted mostly through trade channels) - preparedness of the Polish economy to the euro adoption. Calculations reveal that the IIT intensity in Poland is already relatively high (in particular in relations with the euro area members) and continues to rise. This confirms the increasing complementarity of Poland's economy with the economic structures of the euro area partners which reduces the probability of asymmetric shocks.
Keywords: F11; F12; F15; F44; 650; intra-industry trade; optimum currency area; trade specialization; EU-10 countries; euro area